'My Husband … is an Authentic Psychopath': Spanish Civil War Veterans, Mental Illness and the Francoist Regime. (28th February 2021) - Wright, Stephanie
Summary: This article seeks to broaden current understandings of war psychiatry, particularly within authoritarian contexts, through its focus on mental illness in the Francoist army during and after the Spanish Civil war of 1936–39. More specifically, this research points to the coexistence of multiple discourses of psychological disturbance in Francoist Spain. Francoist psychiatrists were reluctant to acknowledge the psychological fallout of the Spanish Civil War on those soldiers who had helped to ensure the Nationalist victory, and the regime's legislation disenfranchised those who did not boast lengthy military careers. Yet in the absence of an official language of war trauma, veterans and their families found other ways to express themselves, often appropriating the regime's own political and psychiatric discourse. Such popular understandings of Civil War trauma served an important function for Spaniards seeking to negotiate the many contradictions of life under the Francoist regime.